2004
DOI: 10.1158/0008-5472.can-03-3108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Apoptosis Activation Cascade Induced in Mammary Carcinomas by Energy Restriction

Abstract: Energy restriction (ER) inhibits mammary carcinogenesis and results in a marked reduction in tumor size, effects likely to be explained by ER-mediated induction of apoptosis. The goal of this study was to investigate the molecular mechanism(s) accounting for apoptosis induction. To do this, chemically induced mammary carcinomas were evaluated from rats that were ad libitum fed (control), 40% ER, or 40% ER but energy repleted for 7 days before study termination (ER-REP); the ER-REP group permitted the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…This design was chosen based on the fact that at 12 h less than 10% of the cells had entered early apoptosis in response to the combination of both agents. We reasoned that it would be important to define transcriptome changes that occur during the proapoptotic signaling phase rather than those occurring during the execution of the apoptotic program (Castedo et al, 2006;Vitale et al, 2007;de La Motte Rouge et al, 2007), when RNAs (Houge et al, 1995;Nadano and Sato, 2000) and the death-associated bioenergetic collapse (Thompson et al, 2004;Klawitter et al, 2009) (Table 1). The complete list of modified tyrosine kinases is given in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…This design was chosen based on the fact that at 12 h less than 10% of the cells had entered early apoptosis in response to the combination of both agents. We reasoned that it would be important to define transcriptome changes that occur during the proapoptotic signaling phase rather than those occurring during the execution of the apoptotic program (Castedo et al, 2006;Vitale et al, 2007;de La Motte Rouge et al, 2007), when RNAs (Houge et al, 1995;Nadano and Sato, 2000) and the death-associated bioenergetic collapse (Thompson et al, 2004;Klawitter et al, 2009) (Table 1). The complete list of modified tyrosine kinases is given in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…BAD stimulates apoptosis by heterodimerizing with and inactivating the antiapoptotic proteins Bcl-2 and Bcl-x (18,19). DR is known to reduce Bcl-2 and Bcl-xL expression and to increase the expression of Bax, Apaf-1, caspase-9, and caspase-3 in experimental carcinomas, suggesting that DR could inhibit tumor growth in part by inducing mitochondrial-dependent apoptosis mediated by the dephosphorylation of BAD (54). Our findings agree with biochemical and morphologic evidence that DR is proapoptotic in malignant astrocytomas and support evidence that BAD coordinates glucose/IGF-I homeostasis and the induction of apoptosis (7,18,19,31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, caspase-3 activation and PARP cleavage were undetectable under either ad libitum or DR feeding in the U87-MG tumor. Caspase-3 activation is tightly coupled to PARP cleavage in many tumor cell lines and is important for the rapid onset of apoptosis (25,47). Previous studies showed that expression of active caspase-3 does not overlap completely with that of apoptotic nuclei in various human brain tumors, suggesting the participation of caspase-3-independent cell death pathways in these tumors (22,23,48).…”
Section: Discussionmentioning
confidence: 99%